An evaluation of the reduction of heat loss enabled by halloysite modification of oilwell cement. (7th November 2019) - Udayakantha, Malsha; Cho, Junsang; Liu, Kai-Wei; Mukhopadhyay, Anol; Gupta, Subodh; Hong, Claire Y; Banerjee, Sarbajit
Abstract: The increasing reliance on steam-assisted gravity drainage (SAGD) to access unconventional bitumen deposits within the sub-Arctic necessitates the development of robust cement sheaths for oilwell cementing. Such cement sheaths can potentially increase the energy efficiency of the SAGD process by reducing heat loss while maintaining mechanical integrity upon prolonged exposure to cyclic thermal stress. Modifying oilwell cement by the inclusion of hydroxyethylcellulose-functionalized halloysite nanotubes (HEC-HNTs) within the cementitious matrix results in a high density of enclosed void space and disparate interfaces, which serve to scatter phonons and reduce thermal conductivity. In this study, we have systematically evaluated the influence of HEC-HNT loading on the thermomechanical properties of cement with and without the addition of calcium chloride as an accelerator and have correlated the reduction of thermal conductivity to the distinctive microstructure of the nanocomposite cement. The incorporation of HEC-HNTs in thermal cement reduces the thermal conductivity from 0.856 W m −1 ·K −1 to 0.206 W m −1 ·K −1 without substantially altering the compressive strength. Model systems mimicking SAGD oilwell cement sheaths have been prepared from umodified and modified (incorporating HEC-HNT) cement and subjected to cyclic thermal stress emulative of SAGD conditions. Cement sheaths constructed from the modified cement with CaCl2 maintain a higher temperature gradient as compared to unmodified cement with CaCl2 ; a 12 °C increased temperature differential between hot and cold surfaces is observed for a 4.5 cm thick sheath with a considerably shallower rate of increase in temperature. Aggressive thermal cycling (20 h at 250 °C followed by 4 h at 25 °C) for 20 days brings about a 20% reduction of compressive strength. The combination of additives facilitating thermal insulation and mitigating differential shrinkage provides an attractive means of oilwell cementing for SAGD applications wherein cyclic thermal stresses are operational and energy efficiency is of paramount importance. Extrapolating the considerably increased temperature differentials between hot and cold ends within model systems to entire wells portends significant energy savings and reduction in amounts of injected steam.